Solutions for a natural ventilation system - Kock, Amanda; Larsson, Mathilda (My University, 2014)
This project is a cooperation between our Bachelor thesis and a voluntary project in the Amazon region of Colombia. The main purpose is to implement and understand what factors to take into consideration when designing a natural ventilated system in a tropical climate like the Amazon region and at the same time decrease the current indoor pollution that are emitted from cooking areas. By conducting a field study in the area, uncertainties became facts and two physical models were built in a smaller Amazon village. The actions made in the field are supported by calculations and literature through the report. Assessments on several implementable natural vented designs show that the preferable design finally result in two cob ovens, considering economic and environmental sustainability. The advantages are the availability of material, the use of natural ventilation and reduced amount of firewood. Natural ventilation appears to be a good solution for sites like the village in the Amazon region, but careful consideration of design and material is required to produce a feasible and functioning unit. Additionally, it is preferable implementing one stove per household rather than stoves in common areas, because it gives the viable sense of ownership and therefore increases the maintenance. In order to maintain and develop the indoor environment it is also important, for the inhabitants, to be aware of the problem indoor air pollution is causing. Finally, increased awareness about the possibility of implementing solutions that uses natural ventilation leads to smart and simple options where mechanical ventilation is not required.
Keywords: Building Futures; Byggnadsteknik; Building Futures; Building engineering